Does Indonesian COVID-19 Emergency Law Secure Rule of Law and Human Rights? - Herlambang Perdana Wiratraman (Journal of Southeast Asian Human Rights, 2020)
President Joko Widodo announced a public health emergency at the end of March 2020. This policy demonstrates denial, too late and limited in responding to the spread of Covid-19. On the other hand, the state security approach during the pandemic has pressured civil liberties, especially criticisms against government policies. This phenomenon is not a new development in Indonesia whereby attacks on freedom of expression and academic freedom are common. This article analyses how the COVID-19 health emergency situation is handled by the government from the perspective of human rights law standards and the rule of law. This article argues the Indonesian COVID-19 emergency law violates many guarantees of legal protection under the rule of law standard. It is apparent how the issue of human rights has not yet become an effective strategy or approach in this non-natural disaster emergency situation.